Construcción experimental de Celdas Solares Sensibilizadas por Colorante (DSSC) tipo Grätzel. - Arévalo Calderón, Edison Arturo (2015)
Experimental methodology for the construction of dye-sensitized solar cells (DSSC) Grätzel type is performed. It starts by establishing a basic methodology for the design and construction of cells (DSSC); cell is constructed experimentally in the conditions of the city of Loja and finally the cell performance is evaluated experimentally constructed. At the end we can conclude that the cells experimentally constructed give us very good results within hours of high solar radiation.